Diversity of ants across growth stages and months in research field, FASSB P. P.P Tun Razak, Ulu Tekam, Pahang - Syarifah Nadiah; Izfa Riza Hazmi; Idris Abd. Ghani (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
The study on the diversity and abundance of ants in oil palm plantation of different plot ages (1 to 3, 6, 18 and 23 years old) at the Research Field FELDA Agricultural Services Sdn. Bhd, in Ulu Tekam, Jerantut Pahang was conducted. The sample was collected from June to October 2013, using several traps namely malaise trap, pitfall trap and pit-light trap. A total of 57,316 individuals of ants consisting 4 subfamilies, 23 genera and 32 morphospecies were successfully collected. The most abundant and dominant species was Tetramorium sp. (30,975 individuals). Plot 6 years recorded the highest number of ants encountered (22,144) followed by plot 3 years (18,198), plot 1 year (7,011), plot 18 years (5188) and the least was plot 23 years (4775). In term of the species diversity, plot 18 years old recorded the highest diversity (H'=2.51, E'=0.41, R=2.9), while plot 3 years (H’=1.13, E’=0.11, R=2.65) was the least diverse. According to the month of sampling event, September recorded the highest diversity (H'=2.011, E’=0.275, R=3.177) of ant while July recorded the lowest diversity (H’=1.58, E’=0.16, R=2.87). The two-way ANOVA show significant differences in abundance of ants per different plot (ages of plantation) as well according to different month. This study is expected to enhance the information about the diversity of ants in different age of oil palm, especially in Peninsular Malaysia.